1999
DOI: 10.1073/pnas.96.10.5868
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional regulation of plant phosphate transporters

Abstract: Phosphorus is acquired by plant roots primarily via the high-affinity inorganic phosphate (P i ) transporters. The transcripts for P i transporters are highly inducible upon P i starvation, which also results in enhanced P i uptake when P i is resupplied. Using antibodies specific to one of the tomato P i transporters (encoded by LePT1), we show that an increase in the LePT1 transcript under P i starvation leads to a concurrent increase in the transporter protein, suggesting a transcriptional regulation for P … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
125
1
6

Year Published

2001
2001
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 166 publications
(139 citation statements)
references
References 37 publications
7
125
1
6
Order By: Relevance
“…Published reports indicate that, in response to P deficiency, plants may increase synthesis of additional transporter molecules (Drew et al, 1984) or upregulate expression of genes encoding P transporters (Liu et al, 1998;Muchhal et al, 1996;Smith et al, 1997), leading to a subsequent increase in transporter proteins (Muchhal and Raghothama, 1999). The increase of As(V) uptake with P deficiency has been found by Wang et al (2002), which showed that 8 d of P starvation increases the maximal influx of As(V) by 2.5-fold, suggesting an increased density of P/As(V) transporters in the rhizoid cell plasma membranes.…”
Section: Scanning Sitementioning
confidence: 99%
“…Published reports indicate that, in response to P deficiency, plants may increase synthesis of additional transporter molecules (Drew et al, 1984) or upregulate expression of genes encoding P transporters (Liu et al, 1998;Muchhal et al, 1996;Smith et al, 1997), leading to a subsequent increase in transporter proteins (Muchhal and Raghothama, 1999). The increase of As(V) uptake with P deficiency has been found by Wang et al (2002), which showed that 8 d of P starvation increases the maximal influx of As(V) by 2.5-fold, suggesting an increased density of P/As(V) transporters in the rhizoid cell plasma membranes.…”
Section: Scanning Sitementioning
confidence: 99%
“…These results are in agreement with studies in Brassica sp., which showed that Phi reduced the induction of phosphoenolpyruvate phosphatase, pyrophosphate-dependent phosphofructokinase, and highaffinity Pi uptake in Pi-limiting conditions by 40% to 90% (Carswell et al, 1996(Carswell et al, , 1997. We extended our studies to compare the effect of Pi and Phi on steadystate levels of Pi-responsive mRNAs, which encode a Pi transporter, AtPT2 (Muchhal and Raghothama, 1999), an acid phosphatase, AtACP5 (del Pozo et al, 1999), and an unknown gene product, At4 (Burleigh and Harrison, 1999). Our data clearly indicate that Phi represses Pi starvation-inducible gene expression at the transcript level.…”
Section: Table II Repression Of Pi Starvation-inducible Enzymes By Pmentioning
confidence: 99%
“…Although Phi apparently cannot substitute for Pi in terms of meeting the nutritional phosphorus requirements of plants, our data indicate that Phi can substitute for Pi in repressing typical molecular and developmental responses to Pi limitation. Biochemical adaptations to Pi starvation include increased synthesis of anthocyanins, presumably to adjust photosynthetic light reactions to the Pi-dependent Calvin cycle, and increased synthesis of enzymes for scavenging intra-and extracellular phosphorus (Trull et al, 1997;Bosse and Kö ck, 1998;Raghothama, 1999). We previously demonstrated that Pi starvation coordinately induces ribonuclease, phosphodiesterase, and acid phosphatase activities in tomato (Lycopersicon esculentum) cell suspension cultures, which sequentially participate in the complete hydrolysis of exogenous RNA to nucleosides and Pi (Nü rnberger et al, 1990;Abel et al, 2000).…”
Section: Table II Repression Of Pi Starvation-inducible Enzymes By Pmentioning
confidence: 99%
See 2 more Smart Citations